Informing the Agricultural Research Council of Nigeria Amendment Act, 2021 - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The President of Nigeria signed the Agricultural Research Council (ARCN) bill into law in October 2021. Recommendations from IFPRI on ARCN's reorganization were instrumental in the success of this reform.